2003
DOI: 10.3122/jabfm.16.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Prostate-Specific Antigen and Digital Rectal Examination as Screening Tests for Prostate Carcinoma

Abstract: Background: Physicians commonly screen for prostate cancer by using prostate-specific antigen (PSA) and digital rectal examination (DRE). The usefulness of these screening mechanisms is not well established, however. A meta-analysis of PSA and DRE to detect prostate carcinoma was conducted with a focus on sensitivity, specificity, and positive predictive value.Methods: A literature search of OVID database (1966 to November 1999) using the medical subject headings "prostate-specific antigen" and "mass screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
130
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(139 citation statements)
references
References 32 publications
3
130
0
6
Order By: Relevance
“…[28][29][30][31] and neither test has high sensitivity (72.1% and 53.2%, respectively; ref. 32). Some believe that the increasing PSA level is the most informative (33).…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] and neither test has high sensitivity (72.1% and 53.2%, respectively; ref. 32). Some believe that the increasing PSA level is the most informative (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, PSA has severe limitations as a screening test. First, PSA has a low specificity, and its positive predictive value is only approximately 25% in a pooled metaanalysis (3 ), leading to a large number of false-positive results and up to 75% of unnecessary prostate biopsies (4 ). Second, PSA lacks sensitivity, because up to 30% of PCa cases and among these 10% of aggressive PCa cases can be identified in patients with a PSA below 4 g/L (5 ).…”
mentioning
confidence: 99%
“…A volunteer-based study in the US reported specificity of 73% (Punglia et al, 2005). A meta-analysis estimated specificity of PSA as 93% at 4.0 ng ml À1 (Mistry and Cable, 2003). Our study population may represent relatively low-risk men, as the trial is population-based and the subjects are fairly young.…”
Section: Discussionmentioning
confidence: 99%